2021
DOI: 10.1038/s41467-021-25679-0
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function relationship of OqxB efflux pump from Klebsiella pneumoniae

Abstract: OqxB is an RND (Resistance-Nodulation-Division) efflux pump that has emerged as a factor contributing to the antibiotic resistance in Klebsiella pneumoniae. OqxB underwent horizontal gene transfer and is now seen in other Gram-negative bacterial pathogens including Escherichia coli, Enterobacter cloacae and Salmonella spp., further disseminating multi-drug resistance. In this study, we describe crystal structure of OqxB with n-dodecyl-β-D-maltoside (DDM) molecules bound in its substrate-binding pocket, at 1.85… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 79 publications
4
26
0
Order By: Relevance
“…OqxAB efflux pumps are encoded by two OqxA and OqxB genes that are localized in one operon. Plasmid-encoded OqxA and OqxB efflux pumps can confer resistance to several antimicrobial agents, such as fluoroquinolones, chloramphenicol, and tigecycline ( 24 , 25 ). The qacE gene encodes the efflux of antiseptics, mainly quaternary ammonium compounds, and they can be found on plasmids ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…OqxAB efflux pumps are encoded by two OqxA and OqxB genes that are localized in one operon. Plasmid-encoded OqxA and OqxB efflux pumps can confer resistance to several antimicrobial agents, such as fluoroquinolones, chloramphenicol, and tigecycline ( 24 , 25 ). The qacE gene encodes the efflux of antiseptics, mainly quaternary ammonium compounds, and they can be found on plasmids ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The oqx B gene was only observed in our study in the K. pneumoniae isolate phenotypically described as an ESBL producer susceptible to quinolones. While both qnr and oqx genes are plasmid mediated, oqx genes are members of the resistance-nodulation-division (RDN) efflux pump that have been shown to confer resistance to numerous antibiotics in addition to quinolones, including nitrofurantoin, quinoxalines, tigecycline, chloramphenicol, detergents, and disinfectants ( Bharatham et al, 2021 ) and their presence has been shown to accelerate the development of fluoroquinolone resistance in S . Typhimurium ( Wong et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ruggerone and co-workers predicted the location of binding sites within MexB, an AcrB homologue from P. aeruginosa, for the antibiotics meropenem and imipinem, as well as their relative binding affinities [109]. The x-ray structure of the OqxB RND pump from K. pneumoniae, which showed electron density corresponding to n-dodecyl-β-d-maltoside (DDM) molecules in the substratebinding pocket, was augmented by docking and MD simulations from which the binding mode of the fluoroquinolones ciprofloxacin, levofloxacin and moxifloxacin was predicted [110]. Simulations have also contributed to the understanding of the mechanism of action of inhibition of efflux pumps although these are not reviewed here.…”
Section: Rnd Efflux Pumpsmentioning
confidence: 99%